2017
DOI: 10.1128/cvi.00062-17
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Humoral Immune Correlates of Peripartum Transmission of Clade C HIV-1 in the Setting of Peripartum Antiretrovirals

Abstract: Despite the widespread use of antiretrovirals (ARV), more than 150,000 pediatric HIV-1 infections continue to occur annually. Supplemental strategies are necessary to eliminate pediatric HIV infections. We previously reported that maternal HIV envelope-specific anti-V3 IgG and CD4 binding site-directed antibodies, as well as tier 1 virus neutralization, predicted a reduced risk of mother-to-child transmission (MTCT) of HIV-1 in the pre-ARV era U.S.-based Women and Infants Transmission Study (WITS) cohort. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…There is some evidence that V3 nAbs play a role in MTCT, although the results are not consistent across studies and cohorts. V3-specificity was associated with protection in the clade B Women and Infant Transmission Study (7, 8), but not in the clade C Breastfeeding and Nutrition study (11). Based on evidence suggesting that V3-targeting antibodies can select virus escape mutants and drive neutralization resistance in the autologous virus reservoir (30), it has been proposed that maternal V3 nAbs could drive selection of neutralization-resistant transmitted viruses in MTCT (6).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is some evidence that V3 nAbs play a role in MTCT, although the results are not consistent across studies and cohorts. V3-specificity was associated with protection in the clade B Women and Infant Transmission Study (7, 8), but not in the clade C Breastfeeding and Nutrition study (11). Based on evidence suggesting that V3-targeting antibodies can select virus escape mutants and drive neutralization resistance in the autologous virus reservoir (30), it has been proposed that maternal V3 nAbs could drive selection of neutralization-resistant transmitted viruses in MTCT (6).…”
Section: Discussionmentioning
confidence: 95%
“…Relatedly, there is also inconsistency in studies that sought to define properties of Env-specific maternal antibodies that are associated with reduced risk of mother-to-child transmission (MTCT) (6). Some studies suggest that protection is associated with antibodies that target specific epitopes such as variable loop region 3 (V3) (79) or gp41 (10), while another study found no association between nAb properties and MTCT risk (11) and still others have found antibody specificities that are associated with increased infection risk (12).…”
Section: Introductionmentioning
confidence: 99%
“…Protein vaccines and adjuvants. The antigen used for booster immunizations consisted of either C.1086 delta7gp120K160N (gp120) (47,76) or a fusion protein between C.1086 delta7gp120K160N and the Ad2F adhesin (gp120-Ad2F) using a method described previously (26). Briefly, the C-terminal region of Ad2F, from G378 to E582, was used as the transporter/targeting domain.…”
Section: Methodsmentioning
confidence: 99%
“…The antigen used for booster immunizations consisted of either C.1086 delta7gp120K160N (gp120) (45, 46) or a fusion protein between C.1086 delta7gp120K160N and the Ad2F adhesin (gp120-Ad2F) using the method to that previously described (26). Briefly, the C-terminal region of the Ad2F, starting from G378 to E582, was used as the transporter/targeting domain.…”
Section: Methodsmentioning
confidence: 99%